A novel water soluble axially substituted silicon(IV) phthalocyanine bearing quaternized 4-(4-pyridinyl)phenol groups: Synthesis, characterization, photophysicochemical properties and BSA/DNA binding behavior. (15th January 2021) - Al-Raqa, Shaya Y.; Khezami, Khaoula; Kaya, Esra Nur; Durmuş, Mahmut
Graphical abstract: The novel axially bis[4-(4-pyridinyl)phenol] substituted silicon(IV) phthalocyanine and its quaternized derivative were designed and synthesized. The photophysical and photochemical properties of these phthalocyanines were investigated. In addition, a spectroscopic investigation of the binding behavior of the quaternized silicon(IV) phthalocyanine to bovine serum albumin (BSA) and DNA is also presented in this work. Highlights: Synthesis of axially bis[4-(4-pyridinyl)phenol] substituted silicon(IV) phthalocyanine. Synthesis of the water soluble quaternized derivative of this phthalocyanine. The photophysical and photochemical properties of both phthalocyanines were investigated. The bovine serum albumin (BSA) and DNA binding behaviours were determined in this work. Abstract: The novel axially bis[4-(4-pyridinyl)phenol] substituted silicon(IV) phthalocyanine (3 ) and its quaternized derivative (3Q ) were designed and synthesized. These phthalocyanines were fully characterized by elemental analysis and different spectroscopic methods, such as FT-IR, UV–Vis, MALDI-TOF and 1 H NMR. The photophysical and photochemical properties, such as electronic absorption, fluorescence emission, fluorescence lifetimes, singlet oxygen generation and photostability, of these phthalocyanines were investigated. These properties were examined in DMSO for the non-ionic phthalocyanine (3 ) and in both DMSO and aqueous solution for the ionic phthalocyanine (3Q ). The addition of bis[4-(4-pyridinyl)phenol] groups as axial ligands showed an improvement of the photophysical and photochemical properties. In addition, a spectroscopic investigation of the binding behavior of the quaternized silicon(IV) phthalocyanine complex to bovine serum albumin (BSA) and DNA was also studied in this work.